# Solve for v -5/9v=-10

-59v=-10
Multiply both sides of the equation by -95.
-95⋅(-59)⋅v=-95⋅-10
Simplify both sides of the equation.
Simplify -95⋅(-59)⋅v.
Cancel the common factor of 9.
Move the leading negative in -95 into the numerator.
-95⋅(-59)⋅v=-95⋅-10
Move the leading negative in -59 into the numerator.
-95⋅-59⋅v=-95⋅-10
Factor 9 out of -9.
9(-1)5⋅-59⋅v=-95⋅-10
Cancel the common factor.
9⋅-15⋅-59⋅v=-95⋅-10
Rewrite the expression.
-15⋅-5⋅v=-95⋅-10
-15⋅-5⋅v=-95⋅-10
Cancel the common factor of 5.
Factor 5 out of -5.
-15⋅(5(-1))⋅v=-95⋅-10
Cancel the common factor.
-15⋅(5⋅-1)⋅v=-95⋅-10
Rewrite the expression.
-1⋅-1⋅v=-95⋅-10
-1⋅-1⋅v=-95⋅-10
Multiply.
Multiply -1 by -1.
1⋅v=-95⋅-10
Multiply v by 1.
v=-95⋅-10
v=-95⋅-10
v=-95⋅-10
Simplify -95⋅-10.
Cancel the common factor of 5.
Move the leading negative in -95 into the numerator.
v=-95⋅-10
Factor 5 out of -10.
v=-95⋅(5(-2))
Cancel the common factor.
v=-95⋅(5⋅-2)
Rewrite the expression.
v=-9⋅-2
v=-9⋅-2
Multiply -9 by -2.
v=18
v=18
v=18
Solve for v -5/9v=-10

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top